Maternal 25-Hydroxyvitamin D Deficiency Promoted Metabolic Syndrome and Downregulated Nrf2/CBR1 Pathway in Offspring - Zheng, Jianqiong; Liu, Xiaohui; Zheng, Bingbing; Zheng, Zhenzhen; Zhang, Hongping; Zheng, Jiayong; Sun, Congcong; Chen, Haiying; Yang, Jie; Wang, Zuo; Lin, Meimei; Chen, Jingjing; et al. (Frontiers in Pharmacology, 2020)
Metabolic syndrome is a disorder of energy use and storage, which is characterized by central obesity, dyslipidaemia, raised blood pressure and blood sugar levels. Maternal 25-hydroxyvitamin D deﬁciency is known to cause metabolic changes, chronic disease, and increased adiposity in adulthood. However, the underlying mechanism of induced metabolic syndrome (MetS) in the offspring in vitamin D deficient pregnant mothers remains unclear. We identified that maternal 25-hydroxyvitamin D deficiency enhances oxidative stress, which leads to the development of MetS in the mother and her offspring. Further, immunohistochemical, western blotting and qRT-PCR analyses revealed that maternal 25-hydroxyvitamin D deficiency inhibited the activation of the Nrf2/carbonyl reductase 1 (CBR1) pathway in maternal placenta, liver and pancreas, as well as the offspring’s liver and pancreas. Further analyses uncovered that application of 25-hydroxyvitamin D activated the Nrf2/CBR1 pathway, relieving the oxidative stress in BRL cells, suggesting that 25-hydroxyvitamin D regulates oxidative stress in offspring and induces the activation of the Nrf2/CBR1 pathway. Taken together, our study finds that maternal 25-hydroxyvitamin D deficiency is likely to result in offspring’s metabolic syndrome probably via abnormal nutrition transformation across placenta. Depression of the Nrf2/CBR1 pathway in both mothers and their offspring is one of the cause of oxidative stress leading to metabolic syndrome. This study suggests that 25-hydroxyvitamin D treatment may relieve the offspring’s metabolic syndrome.